Survey of non-tunneled temporary hemodialysis catheter clinical practice and training. Issue 5 (September 2019) - Yuan, Christina M; Oliver, James D; Little, Dustin J; Narayan, Rajeev; Prince, Lisa K; Raghavan, Rajeev; Nee, Robert; ,
Background: Nephrologists are placing fewer non-tunneled temporary hemodialysis catheters. Requiring competence for nephrology fellow graduation is controversial. Methods: Anonymous, online survey of all graduates from a single, military nephrology training program (n = 81; 1985–2017) and all US Nephrology program directors (n = 150). Results: Graduate response and completion rates were 59% and 100%, respectively; 93% agreed they had been adequately trained; 58% (26/45) place non-tunneled temporary hemodialysis catheters, independent of academic practice or time in practice, but 12/26 did ⩽5/year and 23/26 referred some or all. The most common reason for continuing non-tunneled temporary hemodialysis catheter placement was that it is an essential emergency procedure (92%). The single most significant barrier was time to do the procedure (49%). Program director response and completion rates were 50% and 79%, respectively. The single most important barrier to fellow competence was busyness of the service (36%), followed by disinterest (21%); 55% believed that non-tunneled temporary hemodialysis catheter insertion competence should be required, with 81% indicating it was an essential emergency procedure. The majority of graduates and program directors agreed that simulation training was valuable; 76% of programs employ simulation. Graduates who had simulation training and program directors with ⩽20 years of practice were significantly more likely to agree that simulation training was necessary. Conclusion: Of the graduate respondents from a single training program, 58% continue to place non-tunneled temporary hemodialysis catheters; 55% of program directors believe non-tunneled temporary hemodialysis catheter procedural competence should be required. Graduates who had non-tunneled temporary hemodialysis catheter simulation training and younger program directors consider simulation training necessary. These findings should be considered in the discussion of non-tunneled temporary hemodialysis catheter curriculum requirements.